Analisis Kondisi Transformator Tenaga dan Rekomendasi Tindak Lanjut Berbasis Health Index - I Made Gusmara Nusaman; Musa Partahi Marbun (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Transformers are essential equipment in electric power transmission systems that function to adjust voltage levels according to system requirements. Over the course of operation, transformer performance may degrade due to aging, loading conditions, and the frequency of disturbances, which can potentially reduce the reliability of power supply. This study examined 22 units of 150 kV GIS-type power transformers with a capacity of 60 MVA located across 8 GIS substations, using a Health Index–based analysis method. The application of the Health Index showed that 19 transformers (86.36%) were in the Good–Very Good category, while 3 units (13.64%) were in the Caution–Very Poor category. Validation was carried out on samples representing the Very Good, Poor, and Very Poor categories, and it demonstrated strong agreement between the Health Index values and the results of inside check, laboratory tests, as well as operational history and further in-depth testing. Correlation analysis indicated a strong negative relationship between the Health Index and transformer operating age (r = –0.821), suggesting that increasing operation age significantly contributes to a decrease in the Health Index value. Based on the analysis, three follow-up actions are recommended: normal operation, operation with intensive and periodic monitoring, and transformer replacement, representing the overall health levels of the transformers in the study sample.